Audição Musical Afetiva: Recurso a expressões faciais para recomendação musical - João Pedro Dias Babo de Carvalho (2018)
It's a hard task to democratise music regarding listeners personal preferences. The processes of music recommendation consider the music consumers in an impersonal way proposing music based in similarities ignoring the emotional context of the listeners. This study evaluates the relation between the facial expressions of the listeners subject to the audition of several songs and their rating regarding personal taste attributed to each of the musical pieces. 26 participants listened to 17 musical excerpts composed by verse and chorus. A Software Development Kit with the aid of a webcam was used to register the facial expressions of each of the participants to obtain data about the presence of emotions during the listening time of each presented song. It was registered a qualitative opinion about each musical theme by all the listeners. Results suggest some apathy regarding emotional states being sometimes in conflict with a regular visual interpretation of facial expressions.